2012
DOI: 10.1523/jneurosci.5110-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Running Speed Alters the Frequency of Hippocampal Gamma Oscillations

Abstract: Successful spatial navigation is thought to employ a combination of at least two strategies: the following of landmark cues and path integration. Path integration requires that the brain use the speed and direction of movement in a meaningful way to continuously compute the position of the animal. Indeed, the running speed of rats modulates both the firing rate of neurons and the spectral properties of low frequency, theta oscillations seen in the local field potential (LFP) of the hippocampus, a region import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
200
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(228 citation statements)
references
References 67 publications
25
200
3
Order By: Relevance
“…2, 3). Slow and fast gamma power estimates were plotted against running speed to examine whether effects were related to differences in running speed, considering that slow and fast gamma are differentially affected by running speed (Ahmed and Mehta, 2012;Kemere et al, 2013;Zheng et al, 2015). Time windows within novel and familiar sessions were also time-matched to account for changes in gamma power that occur across time within a testing session (Bieri et al, 2014; see Materials and Methods, Detection of object exploration periods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, 3). Slow and fast gamma power estimates were plotted against running speed to examine whether effects were related to differences in running speed, considering that slow and fast gamma are differentially affected by running speed (Ahmed and Mehta, 2012;Kemere et al, 2013;Zheng et al, 2015). Time windows within novel and familiar sessions were also time-matched to account for changes in gamma power that occur across time within a testing session (Bieri et al, 2014; see Materials and Methods, Detection of object exploration periods).…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of power spectra across running speeds during object exploration The power spectra were measured across different running speeds as described previously (Ahmed and Mehta, 2012;Zheng et al, 2015;see Figs. 2, 3, 7).…”
Section: Estimation Of Running Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Because beta and gamma epochs are both short-lasting and regionally specific 173,174 , place cells may interact dynamically with a range of entorhinal cell assemblies each carrying a distinct type of information. The efficiency of individual functional inputs depends on behaviour, such as running speed 175 , and evolves in parallel with behavioural learning 174 , suggesting that the balance between inputs to a place cell is experience-dependent.…”
Section: Grid Cells and The Formation Of Place Fieldsmentioning
confidence: 99%
“…In the rat hippocampus, there is a remarkable low-frequency activity, the well-known ''theta rhythm.'' It has been reported that the theta rhythm modulates gamma oscillations (Bragin et al 1995a;Tort et al 2008;Colgin et al 2009;Belluscio et al 2012) and their CFC alters depending on the running speed (Chen et al 2011;Ahmed and Mehta 2012) and the behavioral performance (Tort et al 2009;Shirvalkar et al 2010). Here we particularly focused on the CFC during a delay period, which several studies have suggested to require the involvement of hippocampus for successful task performance (Ainge et al 2007;Pastalkova et al 2008;Takahashi et al 2009a, b;MacDonald et al 2011).…”
Section: Introductionmentioning
confidence: 99%